An assessment of the Assemblies of God, Ghana’s Vision 3000 in light of Venn’s Three-Self Mission Model - Ampofo, Mishael Donkor (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2024.